1995
DOI: 10.1182/blood.v86.2.677.bloodjournal862677
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the dihydrofolate reductase gene is a mechanism of acquired resistance to methotrexate in patients with acute lymphoblastic leukemia and is correlated with p53 gene mutations

Abstract: Although dihydrofolate reductase (DHFR) gene amplification is a common mechanism of resistance to methotrexate (MTX) in tumor cell lines, with the exception of a few case reports, the incidence of this phenomenon as a mechanism of MTX resistance in the clinic has not been reported. We studied 38 untreated patients and 29 patients in relapse with acute lymphoblastic leukemia (ALL) for gene amplification and p53 gene mutations. Three patients were studied both at diagnosis and at each of two relapses after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…For children diagnosed with ALL with WBC counts less than 50 × 10 9 /l, those who expressed elevated DHFR had significantly shorter event‐free survivals (EFS) than those with normal DHFR expression (Matherly et al , 1997). Similarly, elevated DHFR gene copies and transcripts were reported by Goker et al (1995) at relapse compared with diagnosis and, for three patients with paired diagnostic samples, DHFR gene amplification was detected at relapse following MTX therapy.…”
mentioning
confidence: 69%
“…For children diagnosed with ALL with WBC counts less than 50 × 10 9 /l, those who expressed elevated DHFR had significantly shorter event‐free survivals (EFS) than those with normal DHFR expression (Matherly et al , 1997). Similarly, elevated DHFR gene copies and transcripts were reported by Goker et al (1995) at relapse compared with diagnosis and, for three patients with paired diagnostic samples, DHFR gene amplification was detected at relapse following MTX therapy.…”
mentioning
confidence: 69%
“…Cell lines with mutated p53, a tumor suppressor gene, have the capacity to undergo gene amplification after antimetabolite exposure [21,22]. We showed that low-level DHFR gene amplification in blasts from patients with ALL is also associated with p53 gene mutations [17]. Association of low-level DHFR gene amplification with p53 mutations in ALL blasts strengthens the concept that the loss of wild-type p53 function results in the loss of the checkpoint at the G 1 /S boundary and permits cells to enter S phase without repair of DNA damage caused by MTX.…”
Section: Tumor Suppressor Genes and Drug Resistancementioning
confidence: 88%
“…It therefore appears that inactivation of P53 is a mechanism of resistance to anti-neoplastic agents that is independent of mdr 1 mechanism. On the other hand, in relapsing ALL, a strong correlation was found between P53 mutations and amplification of the dihydrofolate reductase gene, implicated in the acquired resistance to methotrexate in this disorder (Goker et al, 1995). It is possible, but not yet demonstrated, that inactivation of the P53 gene, which leads to gene instability, may be a determining factor of this gene amplification.…”
Section: Clinical Relevance Of P53 Mutations In Haematological Malignmentioning
confidence: 99%